2000
DOI: 10.25249/0375-7536.2000302302305
|View full text |Cite
|
Sign up to set email alerts
|

A Metallogenic Evolution Model for the Lead-Zinc Deposits of the Meso and Neoproterozoic Sedimentary Basins of the São Francisco Craton, Bahia and Minas Gerais, Brazil

Abstract: Integrated studies carried out on the Proterozoic sediment-hosted Pb-Zn sulfide deposits of the São Francisco Craton, Brazil, allowed the estimation of (1) ages of the host sequences, (2) timing of mineralization, (3) possible sources of metal and sulfur, (4) temperature and salinity range of mineralizing solutions, (5) sources of fluids and (6) possible mechanisms of fluid flow. Contrary to the deposits from other Proterozoic basins, the Brazilian deposits do not contain world class metal reserves. This can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 6 publications
0
13
0
12
Order By: Relevance
“…However, for deposition in Congo, Hoy and Ohmoto (1989) suggested that the high positive d 34 S values originated from an input of hydrothermal sulphur characterized by a d 34 S $ +9&. The same hypothesis is also proposed for the Meso-and Neoproterozoic lead-zinc deposits of the São Francisco Craton (Misi et al, 2000). Rare d 34 S sulphate analyses from host rocks are $+17& at Mufulira in Zambia (Sweeney et al, 1986) and +22.6& in the Mines Subgroup (average) at Kolwezi (Okitaudji, 1989).…”
Section: Isotopic Geochemistrymentioning
confidence: 77%
See 1 more Smart Citation
“…However, for deposition in Congo, Hoy and Ohmoto (1989) suggested that the high positive d 34 S values originated from an input of hydrothermal sulphur characterized by a d 34 S $ +9&. The same hypothesis is also proposed for the Meso-and Neoproterozoic lead-zinc deposits of the São Francisco Craton (Misi et al, 2000). Rare d 34 S sulphate analyses from host rocks are $+17& at Mufulira in Zambia (Sweeney et al, 1986) and +22.6& in the Mines Subgroup (average) at Kolwezi (Okitaudji, 1989).…”
Section: Isotopic Geochemistrymentioning
confidence: 77%
“…However they show a consistent large range of d 34 S values (Jensen and Dechow, 1962;Dechow and Jensen, 1965;Sweeney et al, 1986;Okitaudji, 1989;Hoy and Ohmoto, 1989;McGowan et al, 2003;Lerouge et al, 2004), from high negative to high positive values, which characterize the sediment-hosted deposits (e.g. Ohmoto and Rye, 1979;Krouse, 1980;Misi et (Sweeney et al, 1986). +17.0 Fig.…”
Section: Isotopic Geochemistrymentioning
confidence: 92%
“…The Morro Agudo lead-zinc mine has reserves at 5 Mt of 6.3% Zn and 2.9% Pb . This deposit has been categorized as a MVT deposit by and Iyer et al(1992); a SEDEX by Misi et al (1996) as well as Freitas-Silva and Dardenne (1997); and an Irish-type by Cunha et al (2000), , Misi et al (2000), and Monteiro (2002).…”
Section: Morro Agudo Lead-zinc Minementioning
confidence: 99%
“…(1992) have interpreted to indicate a mineralization age of 650 ± 50 Ma. Lead isotope data also indicate that lead in the deposits of the Vazante–Unaí trend was derived from very uranium‐ and thorium‐rich source rocks, and that isotopic compositions of the Vazante deposit resemble those of much of the Morro Agudo deposit, indicating a possible genetic relationship (Misi et al . 2000; Cunha et al .…”
Section: Geological Backgroundmentioning
confidence: 99%